CONFLICT RESOLUTION IN THE MECCA–MEDINA WAR: Sirah Nabawiyah Study - M. Affan; Ajid Thohir (IAIN Ponorogo, 2018)
Abstract: This article describe the conflict resolution carried out by the Prophet Muhammad (PBUH) in the Mecca-Medina War. The Mecca-Medina War itself was a war that took place between Mecca Quraysh against the Muslims in the early period of Islamic history. This war took the largest portion of the conflict that occurred throughout Muhammad's prophetic history. The research method used in this study was historical research. The results of this study are expected to contribute ideas in conflict resolution by relying on the history of the Prophet (PBUH). The results of the study indicate that dialogue, migration, peace agreements, ceasefire and amnesty are conflict resolutions carried out by the Prophet (PBUH) in the Mecca-Medina War. The Prophet (PBUH) ended the war against the Quraysh of Mecca by diminishing casualties and narrowing the space for war. In the modern context which radicalism in the name of religion has caused many conflicts, this sirah nabawiyah-based conflict resolution method is quite relevant to be applied in resolving theological-based conflicts in the Muslim World globally.الملخص: سوف تصف المقالة التالية حل النزاع الذي قام به النبي محمد (ص) في حرب مكة المكرمة. كانت حرب مكة-المدينة بحد ذاتها حرباً بين مكة قريش ضد المسلمين في الفترة المبكرة من التاريخ الإسلامي. أخذت هذه الحرب الجزء الأكبر من الصراع الذي حدث طوال تاريخ النبي محمد. طريقة البحث المستخدمة في هذه الدراسة هي طريقة البحث التاريخي مع نهج علم الحرب. من المتوقع أن تسهم نتائج هذه الدراسة بأفكار في حل النزاع بالاعتماد على تاريخ الرسول (صلى الله عليه وسلم). تشير نتائج الدراسة إلى أن الحوار والهجرة واتفاقيات السلام ووقف إطلاق النار والعفو هي قرارات صراع يقوم بها النبي (ص) في حرب مكة المكرمة. مع حل النزاع هذا ، أنهى الرسول صلى الله عليه وسلم الحرب ضد قريش مكة من خلال التقليل من الخسائر وتضييق مساحة الحرب. في السياق الحديث حيث تسبب التطرف باسم الدين في الكثير من الصراعات ، فإن طريقة حل النزاع القائمة على نبراية السرايا ذات صلة بالغة لتطبيقها في حل الصراعات القائمة على أسس لاهوتية في العالم الإسلامي وعلى الصعيد الدولي Abstrak: Artikel berikut ini akan menguraikan mengenai resolusi konflik yang dijalankan Nabi Muhammad Saw. dalam Perang Mekah-Madinah. Perang Mekah-Madinah sendiri adalah perang yang berlangsung antara Quraisy Mekah melawan Kaum Muslimin pada periode awal sejarah Islam. Perang ini mengambil porsi terbesar dalam konflik yang terjadi sepanjang sejarah kenabian Muhammad Saw. Metode penelitian yang digunakan dalam kajian ini adalah metode penelitian sejarah dengan pendekatan ilmu perang. Hasil dari kajian ini diharapkan dapat memberi sumbangan pemikiran dalam resolusi konflik dengan bersandar pada sejarah Nabi Saw. sendiri. Hasil kajian menunjukkan bahwa dialog, hijrah, perjanjian-perjanjian damai, gencatan senjata dan amnesti adalah resolusi konflik yang dijalankan Nabi Saw. dalam Perang Mekah-Madinah. Dengan resolusi konflik tersebut, Nabi Saw. mengakhiri perang melawan Quraisy Mekah dengan meminimalisir korban dan mempersempit ruang cakup perang. Dalam konteks modern dimana radikalisme atas nama agama telah menyebabkan terjadinya banyak konflik, metode resolusi konflik berbasis sirah nabawiyah ini cukup relevan untuk diaplikasikan dalam menyelesaikan konflik berbasis teologi didalam Dunia Muslim maupun dunia internasional.